(3fNH GdPNGFQ aj CMhGd GdLhGgQs - (3eMeO Hf EHQGgje Hf SGYO GdGfUGQj GdSfLGQj, hjYQa HGHf GdCcaGfj, CHh YHO Gddg,J (B749 (3g` s ((3GdbSWfWjfjI s)
(3ChdgG (B:s
(3hHYO hagPG cJGH ajg NdGUI cdGe GdCbOejf hGdeJCNQjf ef GdMceGA s
(3BNQgG (B:s
(3hbO Bf NJe GdcJGH HMeO Gddg JYGdi hGdUdGI Ydi SjOfG eMeO SjO GdeQSdjf hNGJehYdi Bdg hGUMGHg GdefJLHjf s
(3Vef eLehY , JQJjHgG (B: (3ef U (B65 - (3U(B78s
(3GdQSGdI GdChdi de JUhQ hgj EQTGO GdbGUO Edi CSei GdebGUO ddeDda faSg hgPg GdeLehYI ef cJH GdGSJGP YjSi GdeYdha hBdJ Edi GdLGeYIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B299 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B200s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B137 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B215 s
Keywords: (3GdcjejGA h GdWHjYjGJs